The co-epidemic of Dengue and COVID-19 in Brazil: between challenges in their management and the consequences of socioeconomic inequality (Research, Society and Development, 2021)
SARS-CoV-2, the etiological agent of COVID-19, spread worldwide, reaching pandemic status in March 2020. In this scenario, dengue epidemics continue to impact endemic countries. Taking into account an increase in dengue cases worldwide, the COVID-19 pandemic may signal a serious danger to global public health. In some countries the pandemic coincided with already installed dengue epidemics. Thus, understanding the collective constituents of arboviruses in pandemic times is fundamental for a significant analysis. The present work brings a narrative review elucidating important impacts resulting from the co-epidemic and its consequences in a broader perspective. Problems with the differential diagnosis of these infections are aggravating factors for the decision of clinical management and prognosis of infected individuals. In addition, socioeconomic characteristics and ethnicity are fundamental factors for both dengue transmission dynamics and COVID-19. It also stands out, a scenario that represents a high risk of collapse for health services in facing challenges for combating and managing resources. Therefore, we conclude that in order to overcome the crisis of simultaneous epidemics and their serious consequences, historical aspects and their relationship with the conditions of social vulnerability need to be taken into account, in addition to promoting specific actions for their combat.